Hubungan Minat Belajar Online dengan Hasil Belajar Kognitif Siswa Pembelajaran Biologi di SMP Swasta Muhammadiyyah 1 Medan - Halimatussa’diyah, Enni; Hartono, Adi; Adisti, Yuda; Munthe, Dea Wahdania (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aimed to determine the relationship between online learning interest and students' cognitive learning outcomes when studying biology subjects online at SMPS Muhammadiya 1 Medan. The research was carried out on SMPS Muhammadiya 1 Medan, based on the observations of SMPS Muhammadiya 1 Medan, the interest in online learning is still relatively low, and the learning outcomes are relatively low, so it is necessary to conduct online learning.This study belongs to the type of quantitative research. The data analysis used in this study is a product-moment correlation data analysis to understand whether there is a positive correlation between online learning interest and students' cognitive learning outcomes during online study of biology subject at SMPS Muhammadiya 1 Medan. Keywords: student learning outcomes, online learning, learning interest.